2020
DOI: 10.1152/ajpgi.00079.2020
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides transport during fat absorption in rodent small intestine

Abstract: We report direct in vivo confirmation of transcellular lipopolysaccharides (LPS) uptake from the intestine into the portal vein (PV) involving CD36 and lipid rafts, with minor uptake via the canonical chylomicron pathway. The gut hormone glucagon-like peptide-2 (GLP-2) inhibited uptake into the PV. These data suggest that the bulk of LPS absorption is via the PV to the liver, helping clarify the mechanism of LPS transport into the PV as part of the “gut-liver” axis. These data do not support the paracellular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 88 publications
3
25
0
Order By: Relevance
“…LPS is a significant luminal-derived molecule that will enter circulation and directly alter local (gut) regions, triggering inflammation and injury to downstream organs, such as the liver, inflicting further damage [ 127 , 172 ] and enterocyte barrier dysfunction [ 173 ]. Although passage of LPS through the intestinal barrier has long been speculated to occur via paracellular transport, a recent study examining LPS transport across the intestinal barrier during lipid absorption (non-alcohol conditions) observed CD63- and lipid raft-mediated transcellular transport of LPS across the barrier and absorption into the portal vein [ 174 ]. Regardless of the transport method across the barrier, the manifestation of endotoxemia is a common occurrence in individuals with ALD [ 175 , 176 ] and serum LPS levels appear to correlate with the amount of alcohol being consumed [ 177 ].…”
Section: The Mechanisms Of Alcohol-mediated Gut Dysbiosis Intestimentioning
confidence: 99%
See 1 more Smart Citation
“…LPS is a significant luminal-derived molecule that will enter circulation and directly alter local (gut) regions, triggering inflammation and injury to downstream organs, such as the liver, inflicting further damage [ 127 , 172 ] and enterocyte barrier dysfunction [ 173 ]. Although passage of LPS through the intestinal barrier has long been speculated to occur via paracellular transport, a recent study examining LPS transport across the intestinal barrier during lipid absorption (non-alcohol conditions) observed CD63- and lipid raft-mediated transcellular transport of LPS across the barrier and absorption into the portal vein [ 174 ]. Regardless of the transport method across the barrier, the manifestation of endotoxemia is a common occurrence in individuals with ALD [ 175 , 176 ] and serum LPS levels appear to correlate with the amount of alcohol being consumed [ 177 ].…”
Section: The Mechanisms Of Alcohol-mediated Gut Dysbiosis Intestimentioning
confidence: 99%
“…However, before LPS and other gut-derived harmful molecules (ethanol, acetaldehyde, cytolysin, candidalysin [ 178 ], DAMPs, exosomes, etc.) can travel through the portal vein to the liver, the gut-localized immune response will be affected [ 174 ]. For example, an early study examining mice chronically exposed to alcohol demonstrated that the mRNA levels of certain cytokines (IL-1β and TNFα) are upregulated in the ileum by ethanol alone, while others (IL-6 and IL-11) are upregulated in the presence of both ethanol and LPS [ 179 ].…”
Section: The Mechanisms Of Alcohol-mediated Gut Dysbiosis Intestimentioning
confidence: 99%
“…High-fat dietinduced elevation in circulating lipopolysaccharides (LPS) levels are explained by increased paracellular permeability, but in which intestinal segment? Although the density of Gram-negative microbes and thus LPS concentrations in the cecum or colon can be a millionfold or more greater than in the jejunum, it appears that in some instances such as in coprophagic rodents, the proximal small intestinal lumen also has high luminal LPS levels [5], suggesting that segmental differences should be examined in order to determine the segments responsible for absorption of specific substances.…”
mentioning
confidence: 99%
“…For instance, systemic inflammation such as endotoxemia increases small intestinal paracellular permeability to FITC-dextran 4000 (FD4) via the paracellular leak pathway within 3 h, changes that continue for at least 48 h in rats [6]. In contrast, in normal jejunum, data suggest that LPS are transported via transcellular pathways into the portal vein within 15-30 min and lymphatic circulation at 60-90 min following luminal exposure to long-chain fatty acid oleic acid in vivo and in vitro without corresponding changes in paracellular permeability [5], suggesting that proinflammatory bacterial components may physiologically cross the small intestinal epithelium. Therefore, chronically absorbed LPS or other inflammatory factors may trigger low-grade inflammation during high-fat diet consumption causing intestinal subepithelial inflammation, followed by increased paracellular permeability linked to metabolic endotoxemia, fatty liver, obesity and diabetes.…”
mentioning
confidence: 99%
“…Although inflammation is considered as a strong driver for increased gut paracellular permeability, it is not known whether reduced expression of TJ proteins associated with inflammation directly induces translocation of intestinal bacteria and their pathogen-associated molecular patterns (PAMPs) via the intestinal paracellular route [7]. In fact, recent studies by Akiba et al showed that lipopolysaccharide (LPS) derived from Gram-negative bacteria enters the systemic circulation via the epithelial transcellular route, but not via the paracellular pathway [8]. Therefore, administration of poly P may inhibit the development of AP through a mechanism independent of suppressing bacterial translocation despite the enhanced expression of TJ proteins.…”
mentioning
confidence: 99%